Inculcation of Voluntary Blood Donation Behaviour among Medical Students: An Interventional Study (Indian Journal of Public Health Research & Development, 2020)
Context: India faces a huge shortfall in procuring blood and young people are ideal candidates for VoluntaryBlood Donation (VBD). Experiential learning is active learning by doing and this study explores its rolein influencing the Knowledge, Attitude and Behaviour (KAB) of Medical students towards VBD. Aim: Toevaluate the effectiveness of experiential learning on VBD behaviour among medical students. Objectives: 1.To assess the changes in the KAB of medical students towards VBD following the intervention. 2. To assessif such changes are retained over a longer period of time (6 months) among the medical students. Settings& Design: Prospective interventional study at NRIIMS, Vizag. Methods and materials: A sample size of 30was selected by McNemar’s formula for sample calculation. The KAB scores were assessed pre and postintervention. As a part of intervention students were subjected to Experiential Learning by motivating theirpeers (4) for VBD. The KAB scores were reassessed through delayed post-test after 6 months to know thelong term effect. Results: The average score increased from 5.6 to 8.2 for knowledge which was foundstatistically significant (P
Keywords: VBD- Voluntary Blood Donation, RRC- Red Ribbon Club, KAB- Knowledge Attitude Behaviour, Experiential Learning